Assessment of Air Pollution Impact on Micro-Morphological and Biochemical Properties Of Callistemon citrinus (Curtis) Skeels And Lagerstroemia indica L. (Scientific World, 2021)
The urban air pollution is a major environmental concern, particularly in the developing countries and in their major cities. In the present study an attempt has been made to assess the air pollution effect on micromorphological and biochemical parameters of Callistemon citrinus and Lagerstroemia indica. Biochemical parameters were analyzed by using standard protocol. one-way analysis of variance was performed with SPSS software, v. 20.0, and Duncan test (p ≤ 0.05) was used to compare averages of all measured biochemical parameters and micromorpholgical features. There was a decrease in number of stomata of both species at highly polluted site compared to less polluted site (control). Stomatal index of both species was found to be reduced in polluted site when compared to control. The number of clogged stomata was less in control area samples when compared to polluted sample. A number of epidermal cells were significantly decreased at heavily polluted site. Total chlorophyll content and leaf extract pH in both the plants were found to be significantly higher in control sites than in heavily polluted sites. Ascorbic acid, relative water content, and Air Pollution Tolerance Index (ATPI) was found to be significantly higher at more polluted plants than at control. Based on the present study results, Callistemon citrinus emerged as the most tolerant species with the highest APTI. Hence, Callistemon citrinus can be suggested for plantations along the roadside of urban areas for green belt development.